The Relationship Between the Physical Work Environment and The Performance of Oil Palm Harvesting Employees at PT. Alam Jaya Persada - Humairo Aziza; Sri Ngapiyatun; Adi Samyono; Erna Rositah; Arief Rahman; Wartomo (Jurnal Loupe, 2024)
Work productivity is generally influenced by environmental conditions, where good conditions will facilitate the operations of an organization. The aim of the research is to assess the physical working environmental conditions of harvest work at PT. Alam Jaya Persada in Afdeling 2 and 3, knowing the performance of harvest employees, analyzing the relationship between the work environment and the performance of harvest employees in Afdeling 2 and 3. Quantitative method, the data used is direct observation data in the field, questionnaire data and is equipped with company data or documents as well as literature studies obtained from the internet. The research results show that the physical work environment at PT. Alam Jaya Persada is in good condition, as seen from the average employee response score on topographic indicators of 3.9, humidity and temperature of 3.7, cleanliness of the workplace of 3.8, work tools of 4.1, work facilities of 3. .9 means the whole category is good. Performance of harvest employees at PT. Alam Jaya Persada is good, as can be seen from the average employee response score on the quantity, quality and efficiency indicators of 4.2, work discipline of 4.1, all the average score results are good, and have a significant relationship between the physical work environment and performance with a significance value of 0.001 <0.05. A correlation coefficient of 0.413 means that the relationship is quite strong between the work environment and employee performance and is positive, which means that the relationship between the two variables is in the same direction, where the better the physical work environment, the better the employee's performance.